A Multifaceted Surgical Site Infection Prevention Bundle for Cesarean Delivery - Scholz, Robert; Smith, Becky A.; Adams, Marci G.; Shah, Mona; Brudner, Corrinna; Datta, Avisek; Hirsch, Emmet (American Journal of Perinatology, 2019)
Objective Surgical site infections (SSI, including wound infections, endometritis, pelvic abscess, and sepsis) may complicate cesarean section (C/S). We report outcomes before and after the introduction of an SSI prevention bundle that did not include antibiotics beyond routine prophylaxis (cefazolin, or gentamicin/clindamycin for penicillin-allergic patients).Study Design The prevention bundle was introduced following an increase in C/S-associated SSI, which itself was associated with an institutional switch in preoperative scrub from povidone-iodine to chlorhexidine gluconate (CHG)/isopropanol. Components of the bundle included: (1) full-body preoperative wash with 4% CHG cloths; (2) retraining on surgeon hand scrub; (3) retraining for surgical prep; and (4) patient education regarding wound care. Patients delivered by C/S at ≥24 weeks of gestation were segregated into four epochs over 7 years: (1) baseline (18 months when povidone-iodine was used); (2) CHG scrub (18 months after skin prep was switched to CHG); (3) bundle implementation (24 months); and (4) maintenance (24 months following implementation).Results A total of 3,637 patients were included (n = 667, 796, 1098, and 1076, respectively, in epochs 1–4). A rise in SSI occurred with the institutional switch from povidone-iodine to CHG (i.e., from baseline to the CHG scrub epoch, 8.4–13.3%, p < 0.01). Following the intervention (maintenance epoch), this rate decreased to below baseline values (to 4.5%, p < 0.01), attributable to a decline in wound infection (rates in the above three epochs 6.9, 12.9, and 3.5%, respectively, p < 0.01), with no change in endometritis. In multivariable analysis, only epoch and body mass index (BMI) were independently associated with SSI. The improvement associated with the prevention bundle held for stratified analysis of specific risk factors such as chorioamnionitis, prior C/S, obesity, labor induction, and diabetes.Conclusion Implementation of a prevention bundle was associated with a reduction in post-C/S SSI. This improvement was achieved without the use of antibiotics beyond standard preoperative dosing.
Keywords: cesarean section; infection; surgical site infection; prevention of morbidity